Synthesis, Characterization and Antimicrobial, Antioxidant Properties of Some Benzopyrone Derivatives - JAYASHREE, B.S.; K. KUPPAST, BHIMANNA; VENUGOPALA, K.N. (Asian Journal of Chemistry, 2010)
The purpose of present study is to develop potential antimicrobial and antioxidant agents. In this attempt three series of the substituted flavones such as 3-hydroxy flavones (4aj), 3-methoxy flavones (5a-e) and 3-acetyloxy flavones (6ag) were synthesized and characterized by IR, 1H NMR and mass spectral analysis. Test compounds were subjected for the determination of lipophillic parameter and pharmacological activities such as quantitative antibacterial activity and antioxidant activity by MIC (ELISA) and DPPH* method, respectively.